Training manual to fight trafficking in children for labour, sexual and other forms of exploitation : Textbook 1. - Office, International Labor (International Labour Office, 2009)
The Training manual consists of three Textbooks and one exercise book; 1. Understanding child trafficking, 2. Action against child trafficking at policy and outreach levels 3. Matters of process 4. Exercise book. There is also a facilitators' guide on CD-ROM This is a joint ILO, UNICEF and UN. GIFT project.